An introductory course on social identities and their importance in public health. (20th October 2021) - Wandschneider, L; Namer, Y; Siepmann, I; Khutan, R; Otok, R; Middleton, J; Razum, O; Selig, S
Abstract: Background: Social identities - e.g., sex/gender, ethnicity, ability, sexual orientation - and their intersections shape health inequalities in societies. Yet, a systematic, critical integration into public health curricula is lacking, especially in the European region. To address this gap, we developed a curriculum on social identities and their importance in public health in collaboration with ASPHER. Objectives: The curriculum enables students to identify mechanisms of privilege and oppression related to social identities, and to learn how to determine biases within public health structures (and oneself). Moreover, it equips them with tools and skills to address and change biases in their practices to ultimately reduce health inequities. Results: We conceptualized the curriculum in an iterative and participatory process in a group of students, young professionals and senior researchers from different countries in Western Europe and North America. The curriculum covers three core elements: 1) the introduction of concepts and terminology on diversity, equity and social identities in relation to health inequalities, 2) the reflection on the role of public health professionals and their responsibility within this system; and 3) spotlights on specific social identities, e.g., sex/gender or social class. In addition, it provides guidance on teaching methods to empower a broad range of public health professionals to engage with the course materials more easily. Conclusions: The curriculum has the potential to strengthen the capacities of future public health professionals to acknowledge the relevance of social identities and how to respond effectively to contribute to health equity. After piloting and revisions, the course will be made available on an open access platform.